Droits des femmes ou femmes sans droits ? Le féminisme d’État face à la prostitution. - Alban Jacquemart; Milena Jakšić (Genre, Sexualité et Société)
The adoption of the law “to strengthen the fight against the prostitution system and support prostituted persons” on April 13, 2016 signaled the merging of abolitionism and state feminism in France. The supporters of the bill in the National Assembly and Senate were parliamentarians involved in state feminism institutions and presented their argument in terms of women’s rights. Yet, while this law envisions prostitutes first and foremost as undocumented migrants and, as such, victims requiring protection, the rights it grants them are limited and contingent on their desisting from prostitution. State feminism’s appropriation of the prostitution issue highlights the very narrow conception of women’s rights that is defended—one that is both sociologically and historically determined. The parliamentary debate on the bill clearly reveals the fragility and limited autonomy of women’s rights issues within the state apparatus.